5p-6(p-5)+5(q-5)=

Simple and best practice solution for 5p-6(p-5)+5(q-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-6(p-5)+5(q-5)= equation:


Simplifying
5p + -6(p + -5) + 5(q + -5) = 0

Reorder the terms:
5p + -6(-5 + p) + 5(q + -5) = 0
5p + (-5 * -6 + p * -6) + 5(q + -5) = 0
5p + (30 + -6p) + 5(q + -5) = 0

Reorder the terms:
5p + 30 + -6p + 5(-5 + q) = 0
5p + 30 + -6p + (-5 * 5 + q * 5) = 0
5p + 30 + -6p + (-25 + 5q) = 0

Reorder the terms:
30 + -25 + 5p + -6p + 5q = 0

Combine like terms: 30 + -25 = 5
5 + 5p + -6p + 5q = 0

Combine like terms: 5p + -6p = -1p
5 + -1p + 5q = 0

Solving
5 + -1p + 5q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -1p + -5 + 5q = 0 + -5

Reorder the terms:
5 + -5 + -1p + 5q = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -1p + 5q = 0 + -5
-1p + 5q = 0 + -5

Combine like terms: 0 + -5 = -5
-1p + 5q = -5

Add '-5q' to each side of the equation.
-1p + 5q + -5q = -5 + -5q

Combine like terms: 5q + -5q = 0
-1p + 0 = -5 + -5q
-1p = -5 + -5q

Divide each side by '-1'.
p = 5 + 5q

Simplifying
p = 5 + 5q

See similar equations:

| 3(-6)(4)(-2)= | | (6u^3)(-5u^7v^6)= | | 3(-6)(4)(-2)=(-18)(12)(-6) | | 18=6x | | 9y-7(x-y)-x= | | N^2-3+2=0 | | 13x+6-3=12x-3 | | 4(9b+c-5a)-5(a-3c+4b)= | | 33=(3x-8)(7x+4) | | 7(p+7q-13)= | | N^2-13n+40=0 | | 5(6y+12)=6(12y-4) | | 30=-1.2v | | 2x^2+10x-18=0 | | 5(6y+12)=6(12-4) | | -2(4n+4)=2 | | 15x^4-12x^3+3x^2=0 | | y-(-3)=2(x-2) | | (-1)x^3=27 | | 6x+2.72=4.22 | | (1+z)(5z-2)=0 | | 10x+26(x-2)=128 | | 5x+27(x-4)=84 | | 3m+38=9m-4 | | 5m+14=9m-2 | | -6z+2(5-3z)=8(-3z+2)+10 | | 4(p+8q-13)= | | 22-2=6n | | -3k=14-k | | 6y-8(-3)=24 | | 6y-8x=24 | | 5(x+3)=3(7x+3)-2 |

Equations solver categories